Decadence in the Age of Modernism - Murray, Alex, 1980-; Hext, Kate (Book collections on Project MUSE., 2019)
Decadence in the Age of Modernism begins where the history of the decadent movement all too often ends: in 1895. It argues that the decadent principles and aesthetics of Oscar Wilde, Walter Pater, Algernon Swinburne, and others continued to exert a compelling legacy on the next generation of writers, from high modernists and late decadents to writers of the Harlem Renaissance. Writers associated with this decadent counterculture were consciously celebrated but more often blushingly denied, even as they exerted a compelling influence on the early twentieth century. Offering a multifaceted critical revision of how modernism evolved out of, and coexisted with, the decadent movement, the essays in this collection reveal how decadent principles infused twentieth-century prose, poetry, drama, and newspapers. In particular, this book demonstrates the potent impact of decadence on the evolution of queer identity and self-fashioning in the early twentieth century. In close readings of an eclectic range of works by Virginia Woolf, James Joyce, and D. H. Lawrence to Ronald Firbank, Bruce Nugent, and Carl Van Vechten, these essays grapple with a range of related issues, including individualism, the end of Empire, the politics of camp, experimentalism, and the critique of modernity. Contributors: Howard J. Booth, Joseph Bristow, Ellen Crowell, Nick Freeman, Ellis Hanson, Kate Hext, Kirsten MacLeod, Kristin Mahoney, Douglas Mao, Michèle Mendelssohn, Alex Murray, Sarah Parker, Vincent Sherry.